Clinical significance of advanced lung cancer inflammation index, a nutritional and inflammation index, in gastric cancer patients after surgical resection: A propensity score matching analysis. Issue 3 (March 2021) - Yin, Chengzeng; Toiyama, Yuji; Okugawa, Yoshinaga; Omura, Yusuke; Kusunoki, Yukina; Kusunoki, Kurando; Imaoka, Yuki; Yasuda, Hiromi; Ohi, Masaki; Kusunoki, Masato
Summary: Background: The advanced lung cancer inflammation index (ALI) has recently been shown as a prognostic marker for several cancers. However, its predictive value for surgical and oncological outcomes in gastric cancer (GC) remains unclear. Methods: We retrospectively reviewed the preoperative ALI in 620 GC patients receiving gastrectomy to elucidate the prognostic value for overall survival (OS) and disease-free survival (DFS) and to clarify its predictive value for perioperative risk of surgical site infection (SSI) in GC patients. Propensity score matching (PSM) analysis was also conducted to certify these potentials of preoperative ALI. Results: Preoperative low ALI was significantly correlated with advanced tumor–node–metastasis stage classification. Patients with low ALI showed poorer OS (p < 0.0001) and DFS (p < 0.0001) compared to those with high ALI, and multivariate analysis showed that decreased ALI was an independent prognostic factor for OS [hazard ratios of 1.59; 95% confidence interval (CI) of 1.15–2.19, p = 0.006]. Meanwhile, preoperative low ALI was also an independent risk factor for overall SSI [odds ratio (OR) of 2.04, 95% CI of 1.24–3.35, p = 0.005] or organ-space SSI (OR of 2.69, 95% CI of 1.40–5.23, p = 0.003). We further conducted PSM analysis and verified all of these findings in the PSM cohort. Conclusion: Quantification of preoperative ALI can identify patients with high risk of adverse perioperative and oncological outcomes in GC patients.